2009
DOI: 10.1111/j.1468-4004.2009.50512.x
|View full text |Cite
|
Sign up to set email alerts
|

GAMA: towards a physical understanding of galaxy formation

Abstract: The Galaxy And Mass Assembly (GAMA) project is the latest in a tradition of large galaxy redshift surveys, and is now underway on the 3.9m Anglo-Australian Telescope at Siding Spring Observatory. GAMA is designed to map extragalactic structures on scales of 1kpc - 1Mpc in complete detail to a redshift of z~0.2, and to trace the distribution of luminous galaxies out to z~0.5. The principal science aim is to test the standard hierarchical structure formation paradigm of Cold Dark Matter (CDM) on scales of galaxy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
363
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 431 publications
(369 citation statements)
references
References 29 publications
6
363
0
Order By: Relevance
“…Of these 2267 counterparts, 876 have spectroscopic redshifts (spec-zs) acquired either by the SDSS, the Galaxy And Mass Assembly survey (Driver et al 2009), the 2dF redshift survey (Colless et al 2001) or the 6dF redshift survey (Jones et al 2009). For the remaining counterparts, photometric redshifts (photo-zs) were estimated by applying the ANNz neural network code (Collister & Lahav 2004) (UKIDSS; Lawrence et al 2007).…”
Section: Datamentioning
confidence: 99%
“…Of these 2267 counterparts, 876 have spectroscopic redshifts (spec-zs) acquired either by the SDSS, the Galaxy And Mass Assembly survey (Driver et al 2009), the 2dF redshift survey (Colless et al 2001) or the 6dF redshift survey (Jones et al 2009). For the remaining counterparts, photometric redshifts (photo-zs) were estimated by applying the ANNz neural network code (Collister & Lahav 2004) (UKIDSS; Lawrence et al 2007).…”
Section: Datamentioning
confidence: 99%
“…), respectively. The source catalogues are supplemented with cross-identification information from the GAMA survey (Driver et al 2009) and SDSS DR-7 (Abazajian et al 2009) as described in Smith et al (in prep.). For the sources for which spectroscopic redshifts from GAMA or SDSS are not available, we use photometric redshifts generated using the ANNz neural network code (Collister & Lahav 2004), trained with photometry from SDSS and UKIDSS LAS (Lawrence et al 2007), and spectra from the GAMA spectroscopic survey (Driver et al 2009), DEEP2 (Davis et al 2007), zCOSMOS (Lilly et al 2007), and the 2SLAQ-LRG (Cannon et al 2006) survey.…”
Section: Colour-colour Diagramsmentioning
confidence: 99%
“…and 160 μm data from PACS, and 250, 350, and 500 μm data from SPIRE. The H-ATLAS fields include 1 field close to the northern Galactic pole (150 deg 2 ), 3 fields (each 36 deg 2 ) coinciding with the GAMA redshift survey fields (Driver et al 2009), and 2 fields (total area of 250 deg 2 ) near the southern Galactic pole.…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade it has been demonstrated that a panchromatic, X-ray to radio, observational approach is key to develop a consensus on galaxy formation and evolution (e.g., Dickinson et al 2003;Scoville et al 2007;Driver et al 2009Driver et al , 2011Koekemoer et al 2011;Grogin et al 2011). In this context, the radio regime offers an indispensable window toward star formation and supermassive black hole properties of galaxies as radio A&A 602, A1 (2017) continuum emission i) provides a dust-unbiased star formation tracer at high angular resolution (e.g., Condon 1992;Haarsma et al 2000;Seymour et al 2008;Smolčić et al 2009b;Karim et al 2011); and ii) directly probes those active galactic nuclei (AGN) that are hosted by the most massive quiescent galaxies and deemed crucial for massive galaxy formation (e.g., Croton et al 2006;Bower et al 2006;Best et al 2006;Evans et al 2006;Hardcastle et al 2007;Smolčić et al 2009aSmolčić et al , 2015Smolčić 2009;Smolčić & Riechers 2011).…”
Section: Introductionmentioning
confidence: 99%